Awareness and attitude regarding obstetric fistula among married women - Dahal, Babita Devi; Shakya, Jayalaxmi (Journal of Chitwan Medical College, 2020)
Background: Awareness towards the maternal condition has great potential to reduce occurrence of life threatening maternal and child illness. Hence, this study aimed to find out the awareness and attitude regarding obstetric fistula among married women. Methods: A descriptive cross-sectional study was used to find out the awareness and attitude regarding obstetric fistula among 206 married women. Data were collected by using semi structured interview schedule and Likert Scale. Analysis was done by using descriptive statistics. Results: The age range of the respondents was 15-79 years. Among literate 163, 34.4% attended general education, 75% were married at the age of 15-19 years, 50% had their first baby at the age of 15-19 years, 65.0 % had 1-3 babies, 66.0% had home delivery and postnatal visit was 9.5%. In this study 0.9% respondents were found with obstetric fistula and 60.2% had low level of awareness. Regarding the level of attitude, 50.0% had positive attitude. Conclusions: The finding concluded that there is low level of awareness and fifty percentages had negative attitude regarding obstetric fistula among married women so there is need of intervntional awareness program in community.